PENGEMBANGAN LKPD DIGITAL BERDIFERENSIASI PERILAKU LITERASI MATEMATIS BERBASIS MASALAH PESERTA DIDIK KELAS VIII SMP - Nurvia, Alya Arkan (Departemen Matematika, 2024)
The study's overarching goal is to develop online LKPD (Learning and Teaching Materials) that encourages students to demonstrate mathematical literacy in contexts that are uniquely their own. All created materials must be true, useful, and efficient. The Plomp Model serves as the basis for this investigation into development. Nine eighth graders with a range of reading and writing styles participated in this study. Student interview guidelines, questionnaires measuring practicality and validity, and other similar instruments were used. This study found that the LKPD has a validity level of 87.64%, placing it in the category of very valid. In one-on-one assessments, students assessed the practicality of Digital LKPD at 88.19%, while in small group evaluations, the rating was 91.32%. The LKPD is deemed effective according to the pupils' final test scores, which averaged out to 1.34. In this view, digital LKPD sorts problem-based mathematical literacy into three distinct but complementary types: legitimate, practical, and effective.Keywords– LKPD, Differentiated, Mathematical literacy behavior, problems